Changes in microbiological, physicochemical, biochemical and therapeutical characteristics of yoghurt upon the addition of selected medicinal herbs / Afsaneh Najarian - Najarian, Afsaneh (2010)
The effects of herbs on the changes in probiotic growth and metabolism in yoghurt during storage were studied. Angelica sinensis, Codonopsis pilosula, Illicium verum, Lycium barbarum, Momorsdica grosvenori and Psidium gujava water-extracts were co-incubated with pasteurized full cream milk containing Lactobacillus acidophilus, Bifidobacterium, Streptococcus thermophilus and L.casei as starter culture. The addition of herbal water extracts stimulated Lactobacillus sp. growth in P. guajava–yoghurt (126.3±26.3 × 106 CFUml-1) only on day 0 and in L. barbarum–yoghurt from 0 to 3 days (109.3±21.5 to 112.7±28.8×106 CFUml-1 respectively) of refrigerated storage. The growth of S. thermophilus were recorded higher than plain yoghurt for A. sinensis–yoghurt (53.0±9.00×108 CFUml-1), C. pilosula–yoghurt (37.8±22.19 × 108 CFU ml-1) and L. barbarum–yoghurts (day 0 and day 6; 97.0±19×108 CFUml-1 and 42.9±4.8×108 CFUml-1 respectively). Total titratable acid (TTA) of A. sinensis–yoghurt (1.02 ± 0.01) was highest followed by M. grosvenori-, L. barbarum-, I. verum-, C. pilosula-, control- and P.guajava–yoghurts. All herbal-yoghurts had lower pH than plain-yoghurt during storage when they were incubated for 18 hours whereas P. guajava– and L. barbarum-yoghurts showed higher pH than control during storage for yoghurts when incubation was terminated at pH 4.5. The presence of A. sinensis, I. verum and L. barbarum caused an increase in peptide concentration in yoghurts especially on day 7 (28.6±0.4, 30.58±2.2 and 32.0±2.0 mg/ml respectively) vs. control (25.42±1.1 mg/ml). A. sinensis also significantly enhanced the total free amino acids (0.31±0.03 to 0.43±0.12 mM) in water soluble nitrogen (WSN). IC50 for evaluating anti- ACE activity of all yoghurts decreased with time to the minimum value by day 7 of storage followed by gradual increase in IC50 values during the remaining period of storage. All herbal-yoghurts, except C. pilosula-yoghurt, showed lower IC50 values than plain-yoghurt on day 21 of iii storage. Specific activity was also lower on day 7 for all treatments but P. guajava- and C. pilosula-yoghurts extract had less effect to reduce enzyme activity on day 0. Densitometric integrated intensity from SDS-PAGE pattern of yoghurt proteins degradation showed that the first week had the greatest α-casein and β-casein values followed by continuous declined in proteolysis as the storage time progressed. In conclusion adding selected medicinal herbs into yoghurt had the potential to enhance yoghurt fermentation, milk protein proteolysis and reduction in ACE-1 activity in vitro. These herbs may be used as functional additives for the enhancement of yoghurt nutritional and potential therapeutical values.